B. Lynch Davis, H. Bustos Domecq, B. Suárez Lynch and other falsifier writers - Pellicer, Rosa (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In this article, the creation mechanisms of Honorio Bustos Domecq and other apocryphal writers created by Borges and Bioy are described in relation to other fake authors, such as Clara Beter, Eduardo Torres or Sabino Ordás. The modus operandi is very similar in every case, excluding the obvious differences; thus, this “third man” is part of a family of fake writers with which he shares a significant part of qualities.